PENGEMBANGAN PENDIDIKAN PARTISIPATIF SEBAGAI UPAYA MENGHADAPI MASYARAKAT EKONOMI ASEAN - Ika Pasca Himawati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
Asean Economic Community (AEC) is a part of social change will be faced by the nation of Indonesia. On a global scale, MEA is began to the development of strategic sectors such as economic development, the application of information technology and the creation of a conducive socio-cultural in masyarakat.In life, education became the main focus in producing quality human resources. Thus, intelligently filling of opportunities and face the challenges MEA.Therefore, participatory learning, which is based on the individual's involvement in a whole series of learning becomes important to develop. Teachers as educators function as a facilitator and partner simultaneously. The taps in the expression is opened widely and integrative bagisetiap individuals.In the process of the development of participatory learning, experience and reasoning thinking as bases in sharpening social sensitivity is intended to respond to social change. So that individuals are able to see and understand the social reality as a whole. In addition, individuals should be able to read or potential opportunities in the face of the MEA. Thus, the potential will be able to thrive in both the local and global scale. Through the development of participatory education learning, learners are encouraged to be able to be personally critical, creative and innovative. With so may increase the human resources that are responsive and adaptive to social change.